PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS CULTURALLY RESPONSIVE TEACHING DAN TECHNOLOGICAL PEDAGOGICAL CONTENT UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS IV SD INPRES 1 TATURA - Lukman Hakim; Azizah; Ni Made Erviniati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the learning activeness of fourth-grade students at SD Inpres 1 Tatura through the implementation of the Project Based Learning (PjBL) model integrated with Culturally Responsive Teaching (CRT) and Technological Pedagogical Content Knowledge (TPACK). This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of three meetings. The subjects of this study were 26 students from diverse cultural backgrounds. The instruments used included observation sheets, project assessment rubrics, and learning achievement tests. The results showed an increase in students’ learning activeness from 42% in the pre-cycle, to 69% in the first cycle, and 85% in the second cycle. Thus, the implementation of PjBL integrated with CRT and TPACK proved effective in improving students’ learning activeness.